Notas sobre a sala São Paulo e a nova fronteira urbana da cultura - Wisnik, Guilherme; Fix, Mariana; Leite, José Guilherme Pereira; Andrade, Julia Pinheiro; Arantes, Pedro (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2000)
The former Júlio Prestes railway station, designed as the gateway to the coffee capital, was only inaugurated in 1938, after the crisis of 1929, and suffered from neglect for many years. Only now, recently converted into a modern concert hall, has the station apparently come into its own. Home to the new State of São Paulo orchestra, modernized by the conductor John Neschling, the Sala São Paulo is the major symbol of new cultural interventions in the city of São Paulo. In the heart of a run-down urban area known as “ Cracolândia" (crackland), the Sala São Paulo represents a glimpse of civilization in the midst of degradation, and promises to transform the whole surrounding area. More than this, the Sala São Paulo is being hailed as the watershed in a major turn-around in the fortunes of the center of the city: triggering, in addition to other cultural investments, a “ domino effect” in the renewed value and upswing of art and the real estate business. Relations between the State and the private sector, between high art and the real estate market, and the territorial struggle represented by this attempt of the social elites to take back the center of the city with their supposed civilizing project, pervade the history of the Sala São Paulo and are set forth in this article